Tuberculosis and Impact of COVID-19 on Spread of Epidemics in Kazakhstan - Zhandarbek Bekshin; Albert Askarov; Yergali Abduraimov; Aralbek Rsaliyev; Gulmira Bissenova; Nurgul Amirkhanova; Zhadyrassyn Nurbekova; Aliya Temirbekova (Pathogens, 2025)
This study examines the epidemiological situation of tuberculosis (TB) in the regions of the Republic of Kazakhstan over the past seven years (2018–2024), which cover the before-, during- and after-COVID-19 periods, with a focus on the risks of its emergence and spread. The analysis revealed that while TB incidence is declining, mortality remains high in the before- and during-COVID-19 periods, indicating a general decline in population health. The concentration of TB incidence in relation to geographic location was mainly in the northern, western and southern regions. Before COVID-19, TB incidence reached 48.2 cases and mortality reached a maximum of 2.4 cases per 100,000 people. In 2024, the incidence and mortality of tuberculosis significantly decreased to 33.5 (30.5%) and 1.0 (58.3%), respectively, reflecting an improvement in health indicators in the post-pandemic period. In the after-COVID-19 period, in regions with high unemployment, the incidence was higher than in the before- and during-COVID-19 periods. Nevertheless, it is important that the trend in tuberculosis incidence shows positive improvement after the COVID-19 period. In addition, a comparative analysis of tuberculosis incidence trends in different age groups and social factor groups shows that the adult population remains the most vulnerable category among the general population. The above-listed factors, as well as our analysis of tuberculosis incidence, shows that TB incidence does not always correlate with the level of vaccination in different regions of Kazakhstan, indicating a multifactorial influence on the tuberculosis epidemic.